2019
DOI: 10.1038/s41598-019-56531-7
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic, Simultaneous Concentration Mapping of Multiple MRI Contrast Agents with Dual Contrast - Magnetic Resonance Fingerprinting

Abstract: Synchronous assessment of multiple MRI contrast agents in a single scanning session would provide a new “multi-color” imaging capability similar to fluorescence imaging but with high spatiotemporal resolution and unlimited imaging depth. This multi-agent MRI technology would enable a whole new class of basic science and clinical MRI experiments that simultaneously explore multiple physiologic/molecular events in vivo. Unfortunately, conventional MRI acquisition techniques are only capable of detecting and quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…Other authors also observed a similar trend when measuring gadolinium and dysprosium concentrations in murine glioma models using dual contrast-MRF. 16,26 The observed GBCA-induced increase in MRF T 1 heterogeneity varied between tissues. Normal TZ exhibited the greatest variation pre-GBCA, which is expected in this age group, given the high prevalence of benign prostatic hyperplasia (BPH).…”
Section: Discussionmentioning
confidence: 99%
“…Other authors also observed a similar trend when measuring gadolinium and dysprosium concentrations in murine glioma models using dual contrast-MRF. 16,26 The observed GBCA-induced increase in MRF T 1 heterogeneity varied between tissues. Normal TZ exhibited the greatest variation pre-GBCA, which is expected in this age group, given the high prevalence of benign prostatic hyperplasia (BPH).…”
Section: Discussionmentioning
confidence: 99%
“…Future studies will need to elucidate issues such as exploring the optimal values of τM to ensures r1 will be maximal for any value of τR at any imaging field strength, optimizing and introducing new MRI scanning parameters to combat the impact of τR on relaxivity at higher imaging field strengths (i.e., fast field-cycling MRI 50 ), CA homogeneity (i.e., equal number of Gd-CA per DNA nanostructure 21 ), diffusion mechanisms, and sensitivity to endogenous pH changes. In addition, developing even faster MR scanning sequences to accelerate the frequency of image acquisition immediately after CA injection is important to identify the response time of the CA as well as performing the analysis while considering diffusion, (e.g., utilizing Magnetic Resonance Fingerprinting techniques 51 ). In summary, the desirable characteristics of the pH-responsive imotif-conjugated nanoparticles for MR analysis enable another step towards translation of more bioresponsive CAs into future in vivo studies.…”
Section: Resultsmentioning
confidence: 99%
“…Efforts of translating MRF to preclinical investigations have been largely focused on developing MRF methods at high‐fields for imaging small laboratory animals 10–12 . Nonhuman primates are playing an increasingly important role in neuroscience research because of their similarity to humans in physiology, neuroanatomy, cognition, and social complexity.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Efforts of translating MRF to preclinical investigations have been largely focused on developing MRF methods at high-fields for imaging small laboratory animals. [10][11][12] Nonhuman primates are playing an increasingly important role in neuroscience research because of their similarity to humans in physiology, neuroanatomy, cognition, and social complexity. However, quantitative T 1 and T 2 mapping in monkey brain remains time consuming because of the requirement of submillimeter resolution covering a much larger field-of-view (FOV) comparing to rodents.…”
Section: Introductionmentioning
confidence: 99%